Vascular complications in high-performance athletes - Arko, F. R.; Harris, E. J.; Zarins, C. K.; Olcott, C. (Journal of Vascular Surgery, 2001)
PURPOSE: The purpose of this study was to evaluate our experience with the diagnosis and management of vascular injuries in a group of high-performance athletes. METHODS: Between June 1994 and June 2000, we treated 26 patients who sustained vascular complications as a result of athletic competition. Clinical presentation, type of athletic competition, location of injury, type of therapy, and degree of rehabilitation were analyzed retrospectively. RESULTS: The mean age of the patients was 23.8 years (range, 17-40). Twenty-one (81%) patients were men, and five (19%) were women. Athletes included 8 major-league baseball players, 7 football players, 2 world-class cyclists, 2 rock climbers, 2 wind surfers, 1 swimmer, 1 kayaker, 1 weight lifter, 1 marksman, and 1 volleyball player. There were 14 (54%) arterial and 12 (46%) venous complications. Arterial injuries included 7 (50%) axillary/subclavian artery or branch artery aneurysms with secondary embolization, 6 (43%) popliteal artery injuries, and 1 (7%) case of intimal hyperplasia and stenosis involving the external iliac artery. Subclavian vein thrombosis (SVT) accounted for all venous complications. Five of the seven patients with axillary/subclavian branch artery aneurysms required lytic therapy for distal emboli, and six required operative intervention. All popliteal artery injuries were treated by femoropopliteal bypass graft with autogenous saphenous vein. The external iliac artery lesion, which occurred in a cyclist, was repaired with limited resection and vein patch angioplasty. All 12 patients with SVT were treated initially with lytic therapy and anticoagulation. Eight patients required thoracic outlet decompression and venolysis of the subclavian vein. Thirteen arterial reconstructions have remained patent at an average follow-up of 31.9 months (range, 2-74). One patient with a popliteal artery injury required reoperation at 2 months for occlusion of his bypass graft. Eleven of the patients with an arterial injury were able to return to their prior level of competition. All of the patients with SVT have remained stable without further venous thrombosis and have returned to their usual level of activity. CONCLUSIONS: Athletes are susceptible to a variety of vascular injuries that may not be easily recognized. A high level of suspicion, a thorough workup including noninvasive studies and arteriography/venography, and prompt treatment are important for a successful outcome.